2018
DOI: 10.1016/j.aeolia.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

North African mineral dust across the tropical Atlantic Ocean: Insights from dust particle size, radiogenic Sr-Nd-Hf isotopes and rare earth elements (REE)

Abstract: Large amounts of mineral dust are exported from North Africa across the Atlantic Ocean, impacting the atmosphere and ocean during transport and after deposition through biogeochemical processes. In order to characterize the isotopic signature of dust from different seasons and years, in relation to their bulk particle size, and to obtain a general idea of its provenance, Saharan dust was collected using subsurface sediment traps moored in the tropical North Atlantic Ocean in 2012-2013, and by shipboard aerosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 75 publications
4
24
0
Order By: Relevance
“…The REE (rare earth element) signatures of the mineral fraction in our surface samples were used to assess dust source. The REE signatures were homogenous and exhibited a positive Eu/Eu* anomaly analogous to local sources (Supplementary Note 6 , Supplementary Table 14 ) 29 31 thereby excluding distal sources characterized by a negative Eu/Eu* anomaly (Asian 32 and African 33 dust) as significant contributors (Fig. 6a, b ).…”
Section: Resultsmentioning
confidence: 99%
“…The REE (rare earth element) signatures of the mineral fraction in our surface samples were used to assess dust source. The REE signatures were homogenous and exhibited a positive Eu/Eu* anomaly analogous to local sources (Supplementary Note 6 , Supplementary Table 14 ) 29 31 thereby excluding distal sources characterized by a negative Eu/Eu* anomaly (Asian 32 and African 33 dust) as significant contributors (Fig. 6a, b ).…”
Section: Resultsmentioning
confidence: 99%
“…6). Van der Does et al (2016Does et al ( , 2018, however, have recently documented aeolian transport of sand-sized particles to the open ocean, so the earlier finding of Thiede et al (1982) may not necessarily exclude an aeolian origin for mica. Nevertheless, although studies of marine sediments have suggested a relatively great age (Pliocene or Miocene) for the Sahara, there are limitations on the interpretation of an African origin for what is thought to be the aeolian component of such sediments.…”
Section: Introductionmentioning
confidence: 95%
“…It could be possible the triboelectric effect [52] of air passing over the plastic will statically charge the particle and make it attract dust. Van der Does et al (2018) [57] suggest this effect could assist particles to remain aloft. The triboelectric effect may also potentially increase plastic particle's potential to be entrained after ocean expulsion (bubble burst/jet expulsion) and transported, similar to ultragiant dust [52].…”
Section: Plos Onementioning
confidence: 99%